Conformations of Low‐Molecular‐Weight Lignin Polymers in Water. Issue 3 (13th January 2016) - Petridis, Loukas; Smith, Jeremy C.
Abstract: Low‐molecular‐weight lignin binds to cellulose during the thermochemical pretreatment of biomass for biofuel production, which prevents the efficient hydrolysis of the cellulose to sugars. The binding properties of lignin are influenced strongly by the conformations it adopts. Here, we use molecular dynamics simulations in aqueous solution to investigate the dependence of the shape of lignin polymers on chain length and temperature. Lignin is found to adopt collapsed conformations in water at 300 and 500 K. However, at 300 K, a discontinuous transition is found in the shape of the polymer as a function of the chain length. Below a critical degree of polymerization, N c =15, the polymer adopts less spherical conformations than above N c . The transition disappears at high temperatures (500 K) at which only spherical shapes are adopted. An implication relevant to cellulosic biofuel production is that lignin will self‐aggregate even at high pretreatment temperatures. Abstract : Lignin conforms ! Understanding the shape and conformations of low‐molecular weight lignin at pretreatment temperatures is important because the lignin shape strongly influences undesirable lignin binding to cellulose, which represents a major obstacle in the conversion of biomass to biofuels. Based on molecular dynamics simulations of lignin polymers, it is found that lignin in water adopts more spherical conformations with increasing degree of polymerization.